Examination of competitive lanthanide sorption onto smectites and its significance in the management of radioactive waste - Galunin, Evgeny; Alba, María D.; Santos, Maria J.; Abrão, Taufik; Vidal, Miquel (Journal of hazardous materials, 2011)
The competitive effect of La and Lu (analogues of radionuclides appearing in radioactive waste) in the sorption in four smectites was examined. Sorption and desorption distribution coefficients (Kd; Kd,des), and desorption rates (Rdes) were determined from batch tests in two media: deionized water and, to consider the influence of cement leachates, 0.02molL−1 Ca. The competitive effect was lower when high-affinity sites were available, as in the water medium at the lowest range of initial lanthanide concentration, with high Kd for La and for Lu (5–63×104Lkg−1). Lower Kd was measured at higher initial concentrations and in the Ca medium, where Lu showed a stronger competitive effect. This was confirmed by fitting the sorption data to a two-solute Langmuir isotherm. The desorption data indicated that sorption was virtually irreversible for the scenarios with high sorption, with an excellent correlation between Kd and Kd,des (R2 around 0.9 for the two lanthanides). Assuming that radioactive waste is a mixture of radionuclides, and that Ca ions will be provided by the cement leachates, this would reduce the retention capacity of clay engineered barriers.